Isolation and Identification of Î±-Glucosidase Inhibitor From Aspergillus Terreus F38 - Munasaroh, Siti; Tamat, Swasono R; Dewi, Rizna Triana (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
Controlled postprandial glucose level is an important strategy in preventing DM type 2. Inhibitors of Î±-glucosidase have been postulated to be useful agents in managements of DM type 2. This research aims to isolate and identify of Î±-glucosidase inhibitor fromAspergillus terreus F38 by liquid fermentation. The mycelium extract of A. terreus F38showed strong activity against Î±-glucosidase with IC50 value of 9.65 Î¼g/mL. Separation and purification of mycelium ectract yielded compound I (Butyrolactone III). The structure was establish on the basis of spectral analysis, according to the data obtained by NMR and LCMS-MS experiments. Compound I showed potential activity against Î±-glucosidase with IC50 value of 13.87 Â Î¼g/mL. Therefore, the metabolites from A. terreus F38 can be used as lead compound to design potent Î±-glucosidase inhibitory agents.